PORTARIA Nº 218, DE 14 DE DEZEMBRO DE 2021 - Vanessa Cristhina Marconi Zago Ribeiro Scarmagnani (DMPF-e, Brasília, DF, 28 dez . Caderno Administrativo, p. 38., 2021)
Divulga a escala de plantão dos membros e servidores do MPF/MT no mês de novembro de 2021/2022.